Eating Habits, Activity Pattern and Socioeconomic Factors That Affect the Prevalence of Overweight and Obesity among Adolescents in Urban Areas of Enugu State, Nigeria - Nwanneka, Ani Peace; Nkechi, Ene-Obong Henrietta; Orji, Uvere Peter (Pakistan Journal of Nutrition, 2016)
This study was designed to assess the influence of eating habits, activity pattern and socioeconomic factors on the prevalence of overweight and obesity among adolescents in urban areas of Enugu State, Nigeria. A total of 250 adolescents (10-19 years) consisting of 114 males and 136 females were randomly selected from six private and public schools. A structured questionnaire was used to collect information on the background, food habits and activity pattern of the adolescents. Anthropometric measurements (weight and height) of the adolescents were obtained using standard instruments and procedures and used to calculate their Body Mass Index (BMI). The BMI were categorized into obesity, overweight, normal and thinness using the International Obesity Task Force (IOTF) criteria. The WHO adult BMI classification was used to classify the adolescents who were 19 years of age. Data obtained were analyzed using the Statistical Package for Social Sciences (SPSS), version 17. A total of 3.4% overweight and 5.7% obese adolescents were from highest income families. The prevalence of the overweight and obesity among adolescents who skipped breakfast was 13 and 3.7%, respectively. Family income, snacking habit, means of going to school and presence of house helps are important factors that influenced the prevalence of overweight and obesity among adolescents in the study area.